Childhood survivors of high-risk neuroblastoma show signs of immune recovery and not immunosenescence - Lázničková, Petra; Kepák, Tomáš; Hortová-Kohoutková, Marcela; Horváth, Luděk; Sheardová, Kateřina; Marciniak, Rafal; Vacca, Carmine; Šiklová, Michaela; Zelante, Teresa; Rossmeislová, Lenka; Křenová, Zdenka; Štěrba, Jaroslav; et al. (European journal of immunology, 2020)
Neuroblastoma survivors show signs of immunosenescence early after therapy in CD8+ T cell compartment and elevated plasma TNF-α but in later follow-up immune recovery comes into play. Whether the recovery phenotype is long lasting or transient remains to be elucidated, however, late adverse effects often occur in childhood cancer survivors.
Keywords: Humans; neuroblastom; přežívající; Cancer Survivors; rizikové faktory; childhood; Survivors; lidé; immunosenescence; přežívající onkologičtí pacienti; adverse late effects; CD8-Positive T-Lymphocytes; CD8-pozitivní T-lymfocyty; imunosenescence; TNF-alfa; immune recovery; neuroblastoma; Immunosenescence; Tumor Necrosis Factor-alpha; Neuroblastoma; Risk Factors